2020
DOI: 10.1186/s40068-020-00203-3
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of soil loss using remote sensing and GIS-based universal soil loss equation in northern catchment of Lake Tana Sub-basin, Upper Blue Nile Basin, Northwest Ethiopia

Abstract: Background Soil erosion is one of the major environmental challenges and has a significant impact on potential land productivity and food security in many highland regions of Ethiopia. Quantifying and identifying the spatial patterns of soil erosion is important for management. The present study aims to estimate soil erosion by water in the Northern catchment of Lake Tana basin in the NW highlands of Ethiopia. The estimations are based on available data through the application of the Universal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…It is important to point out that some few studies such as; Girmay et al (2020) reported a maximum factor range of 100–311 occupying 1.5 % in Agewmariayam watershed, northern Ethiopia and Balabathina et al (2020) reported a maximum factor of 96.47 occupying 1.6 % of the Lake Tana basin in Ethiopia which further shows the diverse sensitivity of the topographic factor in the region. Additionally, Claessens et al (2008) also found out that the topographic factor was the main factor defining the large potential erosion patterns in East Africa.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…It is important to point out that some few studies such as; Girmay et al (2020) reported a maximum factor range of 100–311 occupying 1.5 % in Agewmariayam watershed, northern Ethiopia and Balabathina et al (2020) reported a maximum factor of 96.47 occupying 1.6 % of the Lake Tana basin in Ethiopia which further shows the diverse sensitivity of the topographic factor in the region. Additionally, Claessens et al (2008) also found out that the topographic factor was the main factor defining the large potential erosion patterns in East Africa.…”
Section: Resultsmentioning
confidence: 94%
“…The response of each MUSLE parameter was measured using a simple deterministic sensitivity analysis approach developed by ( Benaman, 2002 ). Maximum and minimum possible values of each MUSLE factor for this region selected from literature ( Kassam et al, 1991 , Nill et al, 1996 , Balabathina et al, 2020 , Girmay et al, 2020 , Kebede et al, 2021 ) were used in the sensitivity analysis. Initially, the model was run using the basin factor values used as baseline values.…”
Section: Methodsmentioning
confidence: 99%
“…The application of the RUSLE model is simple and applicable in limited data conditions. Because of its suitable capacity and relatively simple computational inputs, RUSLE has been widely used around the world [22,[24][25][26][27][28] including in Ethiopia [71]; Kenya [15]; Zimbabwe [9]; China [29,32]; Japan [6]; India [30,31]; Nepal [33,34]; Sri Lanka [72]; South-East Asian countries (Philippines [73][74][75]; Thailand [76,77]; and Mekong River Basin [3,35,37]. Furthermore, the RUSLE also provides international applicability and comparability for the results and methods, because the model can be adjusted and applied in many parts of the world.…”
Section: Determination Of Rusle Factor Valuesmentioning
confidence: 99%
“…Some recent studies that have applied the RUSLE model to investigate the soil loss from the land use and land cover (LULC) changes include those by Gashaw et al [22]; Mustefa et al [23]; Kidane et al [24]; Gelagay and Minale [25]; Tadesse et al [26]; Balabathina et al [27]; Ayele et al [28] in Ethiopia; Kogo et al [15] in Kenya; Marondedze and Schütt [9] in Zimbabwe; Hui et al [29] in China; Prasannakumar et al [30]; Javed et al [31]; Kolli et al [32] in India; Talchabhadel et al [33]; Koirala et al [34] in Nepal; Thuy and Lee [35] in Vietnam; Plangoen et al [36] in Thailand; and Chuenchum et al [3,37] in Mekong River Basin.…”
Section: Introductionmentioning
confidence: 99%
“…128 However, the USLE/RUSLE was applied at different parts of Ethiopia following similar 129 or different approaches to estimate any of its factors (e.g, [28,[33][34][35][36][37][39][40][41][42][43][44]46,48]).…”
Section: Introductionmentioning
confidence: 99%